Physiological and molecular mechanisms of the response of roots of Pinus massoniana Lamb. to low-temperature stress - Lu, Jingyu; Chen, Hu; Yang, Zhangqi; Sun, Shuang; Luo, Qunfeng; Xie, Junkang; Tan, Jianhui (Frontiers in Plant Science, 2022)
Pinus massoniana Lamb. is the timber species with the widest distribution and the largest afforestation area in China, providing a large amount of timber, turpentine and ecological products. but low temperature limits its growth and geographical distribution. Physiological and molecular studies can well explain the mechanism of P. massoniana response to low temperature. In this study, physiological and biochemical indexes, cell morphology, lignin content, gene regulatory networks, and gene expression patterns of different P. massoniana varieties (cold-tolerant and cold-sensitive) were studied from physiological, biochemical, and molecular perspectives. The results indicated that under low-temperature stress, the cold-tolerant cultivar maintained high contents of osmoregulatory substances, and the root morphology and structure remained intact. In the initial stage of low-temperature stress, the number of differentially expressed genes was 7148, and with the extension of stress time, the number of differentially expressed genes decreased to 1991. P. massoniana might direct its responses to low temperature by regulating phenylpropane metabolism, starch and sucrose metabolism, hormone signaling pathways, and transcription factors. BAM, 4CL, CCoAOMT, PRX5, WRKYs, and hormone synthesis related genes play important roles. P. massoniana cultivars may vary in response mechanisms. In this study, physiological and analytical techniques were used to study the root tip response mechanism of Masson's pine to low temperature stress. The results of this study lay a foundation for in-depth research on the molecular functions of P. massoniana under low-temperature stress conditions.